Country-specific equity market characteristics and foreign equity portfolio allocation - Thapa, Chandra; Poshakwale, Sunil S. (Elsevier Science B.V., Amsterdam., 2012)
Do country-specific equity market characteristics explain variations in foreign equity portfolio allocation? We study this question using comprehensive foreign equity portfolio holdings data and different measures of country-specific equity market factors for 36 host countries. Employing panel data econometric estimations, our investigation shows that foreign investors prefer to invest more in larger and highly visible developed markets which are more liquid, exhibit a higher degree of market efficiency and have lower trading costs. The findings imply that by improving the preconditions necessary for well- functioning capital markets, policymakers should be able to attract higher levels of foreign equity portfolio investments.